1999
DOI: 10.1086/303242
|View full text |Cite
|
Sign up to set email alerts
|

Life‐History Consequences of Divergent Selection on Egg Size inDrosophila melanogaster

Abstract: JSTOR is a not-for-profit service that helps scholars, researchers, and students discover, use, and build upon a wide range of content in a trusted digital archive. We use information technology and tools to increase productivity and facilitate new forms of scholarship. For more information about JSTOR, please contact support@jstor.org..

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
66
2

Year Published

2002
2002
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(70 citation statements)
references
References 47 publications
2
66
2
Order By: Relevance
“…To date, however, there is surprisingly little empirical evidence for such a constraint at the genetic level (Bernardo, 1996;Schwarzkopf et al, 1999;Czesak and Fox, 2003;Fischer et al, 2006). In wild bird populations, for example, so far only three studies have tested for a genetic correlation between egg size and clutch size (Lessells et al, 1989;Garant et al, 2008;Santure et al, 2013), two of which were performed in the same population (Garant et al, 2008;Santure et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…To date, however, there is surprisingly little empirical evidence for such a constraint at the genetic level (Bernardo, 1996;Schwarzkopf et al, 1999;Czesak and Fox, 2003;Fischer et al, 2006). In wild bird populations, for example, so far only three studies have tested for a genetic correlation between egg size and clutch size (Lessells et al, 1989;Garant et al, 2008;Santure et al, 2013), two of which were performed in the same population (Garant et al, 2008;Santure et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Such a trade-off may occur as a consequence of resource limitation or via an underlying genetic constraint. Although many studies have focused on energetic trade-offs, the evidence for a negative genetic correlation between offspring number and per offspring investment is equivocal in many taxa (Lessells et al, 1989;Bernardo, 1996;Schwarzkopf et al, 1999;Czesak and Fox, 2003;Fischer et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In two seed beetles, egg size is highly heritable and the estimates range between 0.22 and 0.91, varying between populations and host plants (Fox et al, 1999). Also laboratory selection experiments have demonstrated that egg size is heritable in insects (Harvey, 1983;Schwarzkopf et al, 1999). Environmental and genetic sources tended to affect egg size to a similar extent, emphasising the importance of considering both types of variation (eg Sinervo and Svensson, 1998;Niewiarowski, 2001).…”
Section: K Fischer Et Almentioning
confidence: 99%
“…This variation is almost certainly adaptive because egg size exhibits latitudinal clines, with larger eggs being produced at higher latitudes, and egg length in laboratory populations evolves in response to temperature alone in the predicted directions (11). Phenotypic variability in egg size has been shown to have a polygenic mode of inheritance (12) and responds to artificial selection on egg length (13). As with many phenotypic characters, the adaptive value of egg size in the wild is not known.…”
mentioning
confidence: 99%